Amine‐Free Synthesis of Cesium Lead Halide Perovskite Quantum Dots for Efficient Light‐Emitting Diodes. (31st October 2016) - Yassitepe, Emre; Yang, Zhenyu; Voznyy, Oleksandr; Kim, Younghoon; Walters, Grant; Castañeda, Juan Andres; Kanjanaboos, Pongsakorn; Yuan, Mingjian; Gong, Xiwen; Fan, Fengjia; Pan, Jun; Hoogland, Sjoerd; et al.
Abstract : Cesium lead halide perovskite quantum dots (PQDs) have attracted significant interest for optoelectronic applications in view of their high brightness and narrow emission linewidth at visible wavelengths. A remaining challenge is the degradation of PQDs during purification from the synthesis solution. This is attributed to proton transfer between oleic acid and oleylamine surface capping agents that leads to facile ligand loss. Here, a new synthetic method is reported that enhances the colloidal stability of PQDs by capping them solely using oleic acid (OA). Quaternary alkylammonium halides are used as precursors, eliminating the need for oleylamine. This strategy enhances the colloidal stability of OA capped PQDs during purification, allowing us to remove excess organic content in thin films. Inverted red, green, and blue PQD light‐emitting diodes (LED) are fabricated for the first time with solution‐processed polymer‐based hole transport layers due to higher robustness of OA capped PQDs to solution processing. The blue and green LEDs exhibit threefold and tenfold improved external quantum efficiency (EQE), respectively, compared to prior related reports for amine/ammonium capped cross‐linked PQDs. The brightest blue LED based on all inorganic CsPb(Br1− x Cl x )3 PQDs is also reported. Abstract : A new synthetic method is reported that enhances the colloidal stability of CsPbX3 perovskite quantum dots (PQDs) by capping solely with oleic acid ligands. Inverted red, green, and blue PQD light‐emitting diodes (LEDs) are fabricated using solution‐processed polymer‐based hole transport layers for the first time. The PQD‐LEDs exhibit up to tenfold improvement in external quantum efficiency compared to prior reports.